Constitutional abnormalities of IDH1 combined with secondary mutations predispose a patient with Maffucci syndrome to acute lymphoblastic leukemia. Issue 12 (24th May 2017) - Hirabayashi, Shinsuke; Seki, Masafumi; Hasegawa, Daisuke; Kato, Motohiro; Hyakuna, Nobuyuki; Shuo, Takuya; Kimura, Shunsuke; Yoshida, Kenichi; Kataoka, Keisuke; Fujii, Yoichi; Shiraishi, Yuichi; Chiba, Kenichi; et al.
Abstract: Maffucci syndrome is a nonhereditary disorder caused by somatic mosaic isocitrate dehydrogenase 1 or 2 ( IDH1 or IDH2 ) mutations and is characterized by multiple enchondromas along with hemangiomas. Malignant transformation of enchondromas to chondrosarcomas and secondary neoplasms, such as brain tumors or acute myeloid leukemia, are serious complications. A 15‐year‐old female with Maffucci syndrome developed B‐cell precursor acute lymphoblastic leukemia (BCP‐ALL). A somatic mutation in IDH1 was detected in hemangioma and leukemic cells. KRAS mutation and deletion of IKZF1 were detected in leukemic cells. Patients with Maffucci syndrome may, therefore, be at risk of BCP‐ALL associated with secondary genetic events that affect lymphocyte differentiation.